EFFECT OF FRESH AND FROZEN EMBRYO TRANSFER METHOD ON FERTILITY SUCCESS IN ASSISTED REPRODUCTION: A COMPARATIVE STUDY - Seyedoshohadaei, Fariba; Rezaei, Masoumeh; Allahveisi, Azra; Rahmani, Khaled; Amirkhani, Zahra (Journal of Postgraduate Medical Institute, 2019)
Objective: To study the fertility success of frozen and fresh embryo transmission methods. Methodology: In this descriptive study, 307 infertile women selected by convenience sampling who were referred to the infertility treatment center of Besat Hospital, Sanandaj, Iran from 2015 to 2016 were treated by intra-cytoplasmic sperm injection. In total, 231 patients received fresh embryos and 76 patients received frozen ones. The results of b-HCG, sonography, miscarriage, and the final result of embryo transfer were analyzed by SPSS software using t-test for quantitative outcomes and Fisher's test and chi-square for qualitative outcomes. Results: The transfer of frozen embryo was more successful than fresh embryo transmission. However, it was not a statistically significant difference (p= 0.16). Besides, the difference in biochemical (p= 0.21) and clinical pregnancy (p= 0.53) between the two methods used to produce fertility was not significant. However, the miscarriage rate in the fresh form of transfer was lower than in the frozen one (p= 0.04). Conclusion: No difference was found in biochemical and clinical pregnancy between frozen and fresh transfer methods. However, the miscarriage rate was more in the frozen transmission.